3D scanners in orthodontics - M. Konvalinková; M. Koťová (Czech Dental Chamber, 2018)
Objective: The aim of the paper is to familiarize the reader with the current status in the possibilities of using 3D scanners in dental and orthodontic practices. Introduction: The digitization of models brings countless benefits, whether it is measurement on models, communication of treatment with other professionals, storage or making them. Material and methodology: Laboratory and intraoral scanners available in the current market. Results: The accuracy and high level of technical parameters of all the scanners described is favorable for use in medical practice. From the laboratory scanners, the 3Shape is a favorite for orthodontists in the Czech Republic for its fast scanning. From intraoral scanners, Trios (3Shape) is the most widely used scanner, and now more and more iTero® for its direct connection to the Invisalign system. Conclusion: 3D scanners are practical helpers for the orthodontists, for patients' pleasurable comfort. They are expanding and facilitating professional communication, and they are also a means of illustrating the progress and variants of therapy for a particular patient. Over the course of several years, they will undoubtedly become a common part of most dental practices.